Study of the scientific production of the antibacterial activity of the chemical compounds of the essential oil of Lippia sidoides - Penteado, Ana Lúcia (Revista do Instituto Adolfo Lutz, 2021)
Lippia sidoides Cham. has widespread use in folk medicine because its essential oil (EO) presents great antibacterial properties. In Brazil, this plant has been introduced in governmental programs for herbal medicine, due to its recognized therapeutic activities. This promoted greater interest in the search for new molecules with antimicrobial activity in this EO which have been described by several authors. Thus, this work aimed to present a study of the scientific production of antibacterial activity of the chemical compounds from L. sidoides essential oil (LSEO). The inclusion criteria were articles which assessed the chemical components and antibacterial activity through the inhibition diameter, Minimum Inhibitory Concentration (MIC), and Minimal Bactericidal Concentration (MBC), published between 2000 and 2020. Of the 996 studies identified, 55 met the inclusion criteria. In descending order, the most frequently detected chemical components found in LSEO were: thymol, p-cymene, and caryophillene. Regarding to the origin, the results showed that the extraction of EO were carried out mainly in the Northeast (55.5%) and Southeast (19%) regions of Brazil; and the part of the plant most used for the production were the leaves. In addition, the essential oil showed strong antibacterial activity against most of the bacteria tested.